The activation and slip of laboratory faults containing gypsum gouge under triaxial stress conditions - Liu, Han; Si, Hu; Yang, Zili; Xu, Dayang (Frontiers in Earth Science, 2025)
Understanding the activation and slip characteristics of faults is essential for the safety and stability of underground engineering. The mechanical behavior of laboratory faults with gouge of specific strength remains unclear. Therefore, triaxial compression tests were performed on saw-cut sandstone specimens containing artificial gypsum gouge. Strength criteria analysis, crack pattern analysis, and fault surface roughness evaluation were conducted to investigate the effects of dip angle, confining pressure, and loading rate on the failure modes and stick-slip characteristics of the faults. The results indicate that as the fault dip increases, the fracture mode transitions from rock damage to shear failure along the saw-cut surface. Fractures within the gypsum fault gouge result in deviations between the measured and theoretical strength values. The magnitude of the normal stress controls the fault surface roughness and the variations in the stress drop during fault activation. An increase in the loading rate results in a transition from stick-slip behavior to stable slip. This study enhances the understanding of fault stability and provides valuable insights into monitoring strategies for underground engineering and earthquake prediction.